2020
DOI: 10.1111/1759-7714.13550
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional printed navigational template for localizing small pulmonary nodules: A case‐controlled study

Abstract: Background Localization of small pulmonary nodules is an inevitable challenge for the thoracic surgeon. This study aimed to investigate the accuracy of three‐dimensional (3D) printing technology for localizing small pulmonary nodules, especially ground‐glass nodules (GGNs). Methods This study enrolled patients with peripheral small pulmonary nodules (≤ 2 cm) who required preoperative localization. In the comparison period, patients underwent both computed tomography‐guided (CT‐G) and 3D‐printing template guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Since 3D printing is an extension of 3D reconstruction, it also has the clinical applications of 3D reconstruction. A previous study used a 3D printed model to help identify small lung nodules with a success localization rate of 95.6% (39).…”
Section: D Reconstruction /3d Printing Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Since 3D printing is an extension of 3D reconstruction, it also has the clinical applications of 3D reconstruction. A previous study used a 3D printed model to help identify small lung nodules with a success localization rate of 95.6% (39).…”
Section: D Reconstruction /3d Printing Technologymentioning
confidence: 99%
“…Furthermore, the combined application of 3D-VATS provides surgeons with a good sense of depth in the operative field, and intraoperative navigation by comparing the virtual lung anatomical structures with the real, reducing the operational difficulty, blood loss, and length of operation (30,(39)(40)(41)(42)(43). In addition to preoperative planning and intraoperative navigation, 3D reconstruction/3D printing is helpful in doctor-patient communication, disease interpretation, and clinical teaching (44).…”
Section: D Reconstruction /3d Printing Technologymentioning
confidence: 99%
“…Localization of radiotracers requires specialized equipment and radiation protection. Some new methods other than CT‐guided localization have been reported in recent years including electromagnetic navigation bronchoscopy (ENB) localization, 27,28 3‐D printing localization, 29‐31 and virtual‐assisted lung mapping (VAL‐MAP) 32 . Although these methods have reportedly achieved satisfactory success rates, their complexity may prevent general use, and studies with larger sample sizes are needed to validate them.…”
Section: Discussionmentioning
confidence: 99%
“…Rui Fu's study also showed that the 3D-printed template navigation localization has a good effect, especially for accurate localization of nodules in the upper lobe of the right lung. However, this technology is affected by respiration and body position, and patients with excessively high BMI may compromise the template fit, thereby affecting the positioning accuracy [ 50 , 51 ]. Another type of 3D-printed template-assisted localization is noninvasive.…”
Section: Preoperative Bronchoscopic Pulmonary Nodule Localizationmentioning
confidence: 99%